Do Combination Antiretroviral Therapy Regimens for HIV Infection Feature Diverse T-Cell Phenotypes and Inflammatory Profiles?. (13th August 2020) - Tincati, Camilla; Mondatore, Debora; Bai, Francesca; d'Arminio Monforte, Antonella; Marchetti, Giulia
Abstract: Immune abnormalities featuring HIV infection persist despite the use of effective combination antiretroviral therapy (cART) and may be linked to the development of noninfectious comorbidities. The aim of the present narrative, nonsystematic literature review is to understand whether cART regimens account for qualitative differences in immune reconstitution. Many studies have reported differences in T-cell homeostasis, inflammation, coagulation, and microbial translocation parameters across cART classes and in the course of triple vs dual regimens, yet such evidence is conflicting and not consistent. Possible reasons for discrepant results in the literature are the paucity of randomized controlled clinical trials, the relatively short follow-up of observational studies, the lack of clinical validation of the numerous inflammatory biomarkers utilized, and the absence of research on the effects of cART in tissues. We are currently thus unable to establish if cART classes and regimens are truly accountable for the differences observed in immune/inflammation parameters in different clinical settings. Questions still remain as to whether an early introduction of cART, specifically in the acute stage of disease, or newer drugs and novel dual drug regimens are able to significantly impact the quality of immune reconstitution and the risk of disease progression in HIV-infected subjects.